Efforts To Prevent Unfair Competition of Bank Notaries - Nynda Fatmawati Octarina; Yulianti Buring Nababan (Publikasi Indonesia, 2023)
In the world of banking several times encountered the problem of unfair competition for bank notaries. Banks only want to use the services of certain notaries, so that other notaries find it difficult and are not given the opportunity to provide their services. The purpose of this research is to find out the efforts made to prevent unhealthy competition from bank notaries. This research is a normative research using statutory and conceptual approaches. Data collection was carried out by means of a literature study. Data analysis was carried out using the deductive method. The results of the study stated that preventing unhealthy competition from notaries could be done by opening up opportunities and information for notaries to get clients who make agreements with banks. In addition, supervision is needed from the Indonesian Notary Association organization, as well as strict law enforcement regarding violations of notary ethics who are proven to have monopolized the service of making agreement deeds in the banking sector.